SPIRITUAL INTELLIGENCE AND ORGANIZATIONAL CLIMATE AS PREDICTORS OF LIFE SATISFACTION OF SECONDARY SCHOOL TEACHERS - Bhullar, Gurmanjit kaur (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2013)
Life satisfaction is not a kind of thing- in itself. Unmistakably, it is dependent on a number of factors like one's physical and mental health, one's aspiration levels achieved, one's perception of the gap between one's targets and the extent to which success has been attained in approaching them, one's capability of adjusting, one's ambitions to the means or resources at one's disposal, and one's overall contentment arrived at subjectively and objectively with the conditions of existence. Life satisfaction is the ultimate goal that human beings strive to achieve in their entire life. It is one of the oldest and most persistently investigated issues in the study of adulthood and teachers are not an exception to it.